1998
DOI: 10.1021/bi9811617
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Synergism between Antimicrobial Peptides Magainin 2 and PGLa

Abstract: The antimicrobial peptides magainin 2 and PGLa, discovered in the skin of the African clawed frog, Xenopus laevis, exhibit marked synergism [Westerhoff, H. V., Zasloff, M., Rosner, J. L., Hendler, R. W., de Waal, A., Vaz Gomes, A., Jongsma, A. P. M., Riethorst, A., and Juretic, D., Eur. J. Biochem. 228, 257-264 (1995)], although the mechanism is not yet clear. They are believed to kill bacteria by permeabilizing membranes. In this study, we examined the interactions of these peptides in lipid bilayers. PGLa, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
289
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(318 citation statements)
references
References 37 publications
(74 reference statements)
28
289
0
1
Order By: Relevance
“…The findings presented here, combined with previous observations that polyphemusin I promotes lipid flip-flop between membrane leaflets but does not induce significant vesicle leakage (5), rule out the torroidal pore (46) and carpet mechanisms of action (47). Differential scanning calorimetry of the pretransition and main gel to liquid-crystalline phase transition of DMPC vesicles at the indicated peptide to lipid molar ratios.…”
Section: Discussionsupporting
confidence: 79%
“…The findings presented here, combined with previous observations that polyphemusin I promotes lipid flip-flop between membrane leaflets but does not induce significant vesicle leakage (5), rule out the torroidal pore (46) and carpet mechanisms of action (47). Differential scanning calorimetry of the pretransition and main gel to liquid-crystalline phase transition of DMPC vesicles at the indicated peptide to lipid molar ratios.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, the nature of the changes to E9 DNase secondary structure is unclear, making it difficult to formulate a mechanism for its translocation. A model for the mechanism of translocation of antimicrobial cationic peptides, such as magainin-2, gramicidin S, cecropin, and melittin, has been proposed by Matsusaki (33). It has been suggested that the peptide binds initially to the membrane surface by electrostatic interactions with the polar head group of the lipids.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation could be the rate at which these pores open and close. In the case of antimicrobial peptides, the time that the pore remains open is on the order of milliseconds or more [20][21][22][23][24] while in the case of the TAT peptides, we have observed that the rate is of the order of a microsecond. If the peptide has a cargo attached to it, such as a protein or a fluorescent dye, the cargo could temporarily block the pore as it translocates, reducing the leakage even further.…”
Section: Translocation Of An Arginine and Pore Formationmentioning
confidence: 99%
“…The total process takes less than a microsecond and the maximum diameter of the pore we observed was approximately 5 nm. The rate at which these pores open and close contrasts with the rate of antimicrobials peptides (order of milliseconds or more [20][21][22][23][24]) whose sequences might be specifically designed to maintain the pore open in microbial membranes for enough time to destroy the ionic concentration gradients and consequently kill the cell. This fast rate could explain why sensible leakage has not been detected [39] and why CPPs are able to translocate by forming pores without killing the host cell.…”
Section: Peptides Diffusion and Closing Of The Porementioning
confidence: 99%
See 1 more Smart Citation